Local Government Relations in Knox County Executive Collaboration and its Impact - J. Ryan Sowell (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2011)
The recent governmental history of Knoxville and Knox County represents an intriguing case study of interest-group-led referendums, corruption, and reform. Recent structural reforms were a direct response to the unethical behavior displayed by some members of the Knox County Commission, but indirectly the changes attempted to address a number of lingering community issues. When placed in the context of the community’s contemporary political history, the reforms' significance becomes apparent. In the past twenty years the greater Knoxville community experienced intergovernmental court battles, a failed unification referendum, a sheriff with unprecedented political clout, and state legislative intervention. Executive leadership has had a major impact on the course of the community’s contemporary history and will continue to be an important factor in local debate to come.
Keywords: Government Relations; Executive Collaboration; Leadership